Research on Pull-through Properties of Polyimide Composites in Hygrothermal Environments - BAI Taolin; CHEN Puhui; KONG Bin; ZHANG Yahui; JIANG Kun; GAN Jian (Hangkong gongcheng jinzhan, 2022)
Composite structures have been widely used in the field of aerospace.In order to study the mechanical properties of composites in hygrothermal environments,the pull-through tests of a type of polyimide composite laminates are carried out under three test environments:cold temperature dry(CTD),room temperature dry(RTD)and elevated temperature wet(ETW).The numerical simulation analysis of the RTD test process is carried out.The pull-through strength and failure mode of two typical laminates are obtained by experiment,and the failure load is predicted by simulation analysis.The results show that the type of polyimide composites have excellent thermal stability.The pull-through strength of the composites under CTD condition is 8.1%~9.0% higher than that under RTD condition,and the pull-through strength of the composites under ETW condition is equivalent to that under RTD condition.The pull-through strength of(30/60/10)ply is slightly higher than(40/50/10)ply.